PENGARUH DISIPILIN KERJA, LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PT. KARYA INDORATA PERSADA - Pasaribu William P Rendy; Roesdi Rosnelly; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The study was conducted at PT. Karya Indorata Persada Usun SukaMakmur Gunung Sahilan, Kampar, Lipat Kain Utara, Bangkinang, KabupatenKampar, Riau. This study aims to determine the effect of work discipline, workenvironment and leadership on job satisfaction of employees of PT. KaryaIndorata Persada. In this study there are 4 variables: Work discipline (X1), workenvironment (X2), leadership (X3) and job satisfaction (Y). The population in thisstudy were employees of PT. Karya Indorata Persada with a total of 58respondents. Data collection in this study is by giving questionnaires torespondents and also added with data from the company. The analytical methodused in this study is multiple regression analysis using SPSS (Statistical Packagefor Social Science) version 21. The results of this study indicate that workdiscipline, work environment and leadership have a significant effect on jobsatisfaction. Work discipline has a significant effect on job satisfaction. The workenvironment has a significant effect on job satisfaction. Leadership has asignificant effect on job satisfaction.Keywords : Work Discipline, Work Environment, Leadership, Job Satisfaction.